2002
DOI: 10.1677/joe.0.1740007
|View full text |Cite
|
Sign up to set email alerts
|

Statin-induced apoptosis of vascular endothelial cells is blocked by dexamethasone

Abstract: Statins block de novo synthesis of cholesterol by inhibiting the enzyme, HMG CoA reductase. The product of this reaction, mevalonic acid, is also a precursor of isoprenoids, molecules required for the activation of signalling G-proteins, such as Ras. Signal transduction pathways involving Ras are important for cell survival and this may be why statins induce apoptotic death of several cell types. Given that statins are used to treat vascular disease, it is surprising that no studies have been conducted on vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 32 publications
5
31
2
Order By: Relevance
“…Although numerous studies have investigated the association between Ran and prostate cancer (23), more recent studies have investigated Ran in the context of benign proliferation of prostate cells (24,25). In the present study, the upregulation of the Ran gene was confirmed using RT-PCR, and the results suggested that Ran upregulation may contribute to prostate cell proliferation in BPH.…”
Section: Genesupporting
confidence: 63%
“…Although numerous studies have investigated the association between Ran and prostate cancer (23), more recent studies have investigated Ran in the context of benign proliferation of prostate cells (24,25). In the present study, the upregulation of the Ran gene was confirmed using RT-PCR, and the results suggested that Ran upregulation may contribute to prostate cell proliferation in BPH.…”
Section: Genesupporting
confidence: 63%
“…Given these diverse pathways and anatomically distant events, what evidence exists to suggest that statin therapy (or 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors) might affect any of these pathological events? Matrix remodelling MM Reduced lung parenchymal destruction and MMP 9 activity in smoke exposed rat lung [74,75] HM ex vivo (bronchial epithelial Increase apoptosis in human vascular endothelial cells [84,86] Oxidant response HM in vivo (PMN) Reduce IL-8 release from neutrophils and neutrophil derived reactive oxidant species [77] HM in vivo (serum), MM Strong anti-oxidant properties [87,88] Mucus production MM Reduced LPS-induced goblet cell hyperplasia in bronchial epithelium and Muc5A induced mucus hypersecretion community acquired pneumonia (table 2) [102][103][104][105][106][107][108][109]. However, unlike the studies in COPD, the results in pneumonia are not consistent.…”
Section: Copd and Systemic Inflammationmentioning
confidence: 99%
“…Studies have shown that statins reduce neutrophil influx in the lung which might have a strong effect on attenuating the downstream inflammatory events, such as macrophage influx, lymphocyte activation and inhibition of cytokine release, in particular IL-8 that appears central to the neutrophil inflammation of the lung [67][68][69][70][71][72][73][74][75][76][77][80][81][82][83][84][85][86][87][88]. The inhibition of IL-6, IL-8 and GM-CSF expression by statins has been shown in cell cultures of human BEC [65,70].…”
Section: Statin Effects On Pulmonary Inflammation In Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, statins attenuate production of pro-inflammatory cytokines, inhibit MMP activation and induce apoptosis in variety types of cells 5 . We hypothesized that simvastatin can regulating human lung fibroblast function in wound repair and tissue remodeling following inflammatory lung injury through inhibiting MMP release from the fibroblast in collagen gel.…”
Section: Original Articlementioning
confidence: 99%